The discriminant validity of single-question assessments of subjective cognitive complaints in an Asian older adult population - Pang, Ting; Zhao, Xuhao; He, Xindi; Kan, Cheuk Ni; Venketasubramanian, Narayanaswamy; Cheng, Ching-Yu; Yuan, Changzheng; Chen, Christopher; Xu, Xin (Frontiers in Aging Neuroscience, 2022)
Objective: To compare the discriminant validity of 3 different single-question assessments of subjective cognitive complaints (SCC) for dementia in a community-based older adult population in Singapore. Methods: Eligible older adults aged≥60 were recruited into phase I using the Abbreviated Mental Test (AMT) and progressive forgetfulness question (PFQ). Participants who failed either tests entered phaseⅡand were administered SCC assessments, including the 8th question on the patient Ascertain Dementia 8(AD8-8pt), informant AD8 (AD8-8info), and the 10th item on the Geriatric Depression Scale (GDS-10), followed by the Montreal Cognitive Assessment(MoCA) and a formal neuropsychological battery. Differences in characteristics among diagnostic groups were compared. All discriminatory indices (sensitivity, specificity, positive and negative predictive values, overall accuracy) for these SCC assessments and their combinations with the MoCA were calculated and reported. Results: A total of 3780 participants were assessed at phase I, of which 957 entered and completed phase II. Of whom, 911 were dementia-free and 46 had dementia. The MoCA(13/14) displayed good sensitivity (95.6%), specificity (81.5%) and overall accuracy (82.1%) for dementia detection. The GDS-10 and AD8-8pt showed poor discriminant validity, whilst AD8-8info had the highest specificity(83.2%) and the greatest overall accuracy(82.5%). Compensatory Combination of the AD8-8info with MoCA, the sensitivity and positive predictive values were optimized(100%), whilst the conjunctive combination of 2 tools achieved excellent specificity(96.3%) and overall accuracy(94.8%) in discriminating dementia patients. Conclusions and Implications: Combining a reliable single-question SCC assessment with an objective tool can efficiently discriminate dementia patients from healthy older adults in the community.